2009
DOI: 10.1115/1.3068327
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Blade Platform Film Cooling With Typical Stator-Rotor Purge Flow and Discrete-Hole Film Cooling

Abstract: This paper is focused on the effect of film-hole configurations on platform film cooling. The platform is cooled by purge flow from a simulated stator-rotor seal combined with discrete-hole film cooling within the blade passage. The cylindrical holes and laidback fan-shaped holes are assessed in terms of film-cooling effectiveness and total pressure loss. Lined up with the freestream streamwise direction, the film holes are arranged on the platform with two different layouts. In one layout, the film-cooling ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Woodmansee and Dutton [27] gave four treatment methods to reduce the influence of temperature. Gao et al [28] also presented the method to eliminate the influence of temperature. Actually, the emitting light intensity can be described as Eq.…”
Section: Fig 1 Schematic Of the Test Facilitiesmentioning
confidence: 97%
“…Woodmansee and Dutton [27] gave four treatment methods to reduce the influence of temperature. Gao et al [28] also presented the method to eliminate the influence of temperature. Actually, the emitting light intensity can be described as Eq.…”
Section: Fig 1 Schematic Of the Test Facilitiesmentioning
confidence: 97%
“…More recently, the improvement in film cooling due to the usage of shaped holes in the end-wall has been studied by Barigozzi et al (2007), Colban et al (2008) and Gao et al (2009a). The effect of coolant density ratio on film cooling effectiveness was studied by Narzary et al (2009), with the conclusion that higher density coolants are more resilient to lift-off and result in higher film cooling effectiveness.…”
Section: Endwall Film Coolingmentioning
confidence: 99%
“…Wright et al (2009) tested the effect of upstream wakes generated by wake rods and delta wings to simulate the effect of upstream stator wakes and end-wall vortices, with the conclusion that the delta wings produce a larger negative effect on film cooling. Gao et al (2009a) ran tests on a turbine blade end-wall filmcooling under moderate Mach number conditions (Ma in =0.27 and Ma ex =0.44. Combined purge and discrete hole film cooling with DR = 1.0 was studied by the PSP technique.…”
Section: Endwallmentioning
confidence: 99%
“…He indicated that geometric parameters had a significant influence on the endwall cooling effectiveness, and developing novel shaped holes was still an important way to increase the cooling effectiveness. The study by Gao et al [7] indicated that shaped holes presented a higher cooling effectiveness and wider coolant coverage on the blade platform than normal cylindrical holes, especially at higher blowing ratios. They found that the shaped hole contributed to enhance the lateral expansion of the coolant jet, resulting in larger coolant coverage.…”
Section: Introductionmentioning
confidence: 99%